Dynamics of progressive leadership: exploring engagement and interpersonal communication in education - Ahmad Teguh Purnawanto; Siti Rahmalia Natsir; Bambang Sumardjoko; Harun Joko Prayitno; Sabar Narimo; Niluvar Khodjaeva (Jurnal Studi Komunikasi, 2024)
The transformational educational leadership approach that inspires and motivates teams to achieve extraordinary results is not devoid of any challenges. Educational leaders must be progressive in innovation, inclusiveness, and adaptation to the changing times. They must skilfully communicate emerging challenges to help teams in the educational environment. Perception differences lead to conflicts, thus impacting team communication and collaboration, which in turn affects the achievement of organisational or institution’s goals. This study aims to determine the role of interpersonal communication skills in progressive educational leadership and outline the patterns of interpersonal communication associated in progressive educational leadership. Through the use of narrative literature review methods, these studies show that educational leadership must be progressive in facing the challenges of changing times, and the need for interpersonal communication skills to make this happen. Interpersonal communication is an important element in progressive educational leadership. Many scholarly sources have been reviewed and analysed to support these findings. The study identifies key interpersonal communication skills in progressive educational leadership, such as active listening, clear messaging, empathy, respect for diversity, team collaboration facilitation, effective feedback provision, evidence-based communication, conflict resolution, and the ability to inspire and motivate staff and students. In addition to providing a comprehensive overview of interpersonal communication in progressive educational leadership.